What makes a champion? Early multidisciplinary practice, not early specialization, predicts world-class performance - Güllich, A.; Macnamara, B. N.; Hambrick, D. Z. (Perspectives on psychological science, 2021)
What explains the acquisition of exceptional human performance? Does a focus on intensive specialized practice facilitate excellence, or is a multidisciplinary practice background better? We investigated this question in sports. Our meta-analysis involved 51 international study reports with 477 effect sizes from 6,096 athletes, including 772 of the world`s top performers. Predictor variables included starting age, age of reaching defined performance milestones, and amounts of coach-led practice and youth-led play (e.g., pickup games) in the athlete`s respective main sport and in other sports. Analyses revealed that (a) adult world-class athletes engaged in more childhood/adolescent multisport practice, started their main sport later, accumulated less main-sport practice, and initially progressed more slowly than did national-class athletes; (b) higher performing youth athletes started playing their main sport earlier, engaged in more main-sport practice but less other-sports practice, and had faster initial progress than did lower performing youth athletes; and (c) youth-led play in any sport had negligible effects on both youth and adult performance. We illustrate parallels from science: Nobel laureates had multidisciplinary study/working experience and slower early progress than did national-level award winners. The findings suggest that variable, multidisciplinary practice experiences are associated with gradual initial discipline-specific progress but greater sustainability of long-term development of excellence.